SPEECH ACT ANALYSIS OF "FROZEN" THE MOVIE SCRIPT - Adinda Srimulya Rahayu; Trisnendri Syahrizal; Irma Savitri Sadikin (PROJECT (Professional Journal of English Education), 2019)
This research aimed to analyze the speech acts of the movie script entitled Frozen, the movie that is being the most popular movie in 2013 until now. The research design in this paper is a qualitative method where the writers describe the result in a form of the words and the explanation of the result. The writers analyze all types of speech acts (representatives, commissives, directives, declarations, expressives, verdictives) by Finegan (2011) in doing this research, as the results of this research, all of the types of speech acts had their own meaning  for delivering the sentences to make such a response. The writers found 294 clauses that contain the type of speech acts, there are representatives (37), commissives (3), directives (32), expressives (10). Each type of the speech acts are delivering different meaning. The results of the research are taken from the script of the character named Anna in Frozen the movie.  Keywords:  Pragmatic, Language, Speech Act, Movie